PEMBELAJARAN PAI ERA COVID-19 DI RANTAUPRAPAT, KABUPATEN LABUHANBATU - Leli Hasanah Lubis (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2022)
Learning Religion (Islam) is the primary need of children in the scientific aspect. The morality and morals of children are more or less formed through Islamic Education learning that they receive from parents, teachers, society and adults. For this reason, PAI learning is still needed by children in any condition, including the Covid-19 era. This paper aims to analyze the learning of PAI in the Covid-19 era in RanntauPrapat,kabupaten Labuhanbatu. The formulation of this study focuses on discussing how learning methods, teaching objectives, learning objectives and materials provided by educators during the Covid-19 era in RantauPrapat,Kabupaten Labuhanbatu. The data was collected using a qualitative approach using field study methods (observation, interviews, documentation). The results of this study found that (1) the learning method was carried out by discussion, question and answer, and inviting students to study at the teacher’s house; (2) learning objectives so that children continue to receive religious advice through Islamic Education learning; (3) learning objectives are aimed at elementary age children; and (4) the material taught is a combination of the content of the PAI curriculum and local wisdom in the RantauPrapat,Labuhanbatu